A Pre-Designed Study of The Ethylene Dichloride Plant from Ethylene and Chlorine with 40,000 tons/year Capacity - Sudarto M. Abukasim, Faida Zuhria, Zubair Saing (International Journal of Advanced Science and Technology, 2020)
Ethylene dichloride (EDC) or 1,2 dichloroethane (C2H4Cl2) is used in industry as a raw material for vinyl chloride monomers (VCM) and intermediates in polyvinyl chloride (PVC) production. Besides, the EDC is also used in TEL components, which are mixed in an anti-knock mixture; solvents for oils, waxes, and coating removers (coat cleaners); and raw materials for diamine ethylene, perchlorate ethylene, carbon tetrachloride, and trichloroethylene. The EDC needs in the world have increased since 1985 with the increasing demand for vinyl chloride and polyvinyl chloride. Based on the Indonesian Central Bureau of Statistics data until the end of 2005, Indonesia exports EDC from producing countries such as the USA, Japan, and European countries. Therefore, to meet the lack of domestic EDC requirements, the establishment of the EDC plant was considered. Ethylene dichloride can be produced from ethylene and chlorine. Ethylene can be obtained from Candra Asri Plant in Cilegon and chlorine obtained from Sulfindo Adi Venture Plant. Based on domestic and foreign EDC requirements consideration, existing plant capacity, availability of raw materials, and range capacity for EDC plants is between 9,000-46,000 (Faith and Keyes, 1957). It is the design of this EDC plant with a size of 40,000 tons/year. Based on a review of low operating conditions (temperature and pressure) and the factory presence previously made, the Ethylene dichloride (EDC) plant is classified as low risk. Economic evaluation calculations result in the show: 1) Percentage of Return of Investments (ROI) before tax of 35; 2) Pay Out Time (POT) before tax is 2.24 years; 3) Break-Even Point (BEP) is 41.35%; 4) Shut Down Point (SDP) of 21.7%; 5) Discounted Cash Flow (DCF) of 25.56%. The bank's interest rate in 2018 was 8%, so the DCF was more significant than the bank's loan interest rate. This results based on Aries and Newton's (1955) economics criteria, which concluded that the EDC plant establishment is low-risk. Furthermore, the Ethylene dichloride (EDC) plant of ethylene and chlorine with a 40,000 ton/year production capacity is feasible.